Regression of the lateral oviducts during the larval-adult transformation of the reproductive system of Melipona quadrifasciata and Frieseomelitta varia - Boleli, Isabel Cristina [UNESP]; Paulino-Simões, Zilá Luz; Bitondi, Márcia Maria Gentile (Wiley, 2000)
Toward the end of the larval phase (pre-pupa), the reproductive systems of Melipona quadrifasciata and Frieseomelitta varia workers are anatomically similar. Scanning electron microscopy showed that during this developmental phase the right and left ovaries are fused and form a heart-shaped structure located above the midgut. Each ovary is connected to the genital chamber by a long and slender lateral oviduct. During pupal development, the lateral oviducts of workers from both species become extremely reduced due to a drastic process of cell death, as shown by transmission electron microscopy. During the lateral oviduct shortening, their simple columnar epithelial cells show some signs of apoptosis in addition to necrosis. Cell death was characterized by cytoplasmic vesiculation, peculiar accumulation of glycogen, and dilation of cytoplasmic organelles such as mitochondria and rough endoplasmic reticulum. The nuclei, at first irregularly contoured, became swollen, with chromatin flocculation and various areas of condensed chromatin next to the nuclear envelope. At the end of the pupal phase, deep recesses marked the nuclei. At emergence, worker and queen reproductive systems showed marked differences, although reduction in the lateral oviducts was an event occurring in both castes. However, in queens the ovarioles increased in length and the spermatheca was larger than that of workers. At the external anatomical level, the reproductive system of workers and queens could be distinguished in the white- and pink-eyed pupal phase. The metamorphic function of the death of lateral oviduct cells, with consequent oviduct shortening, is discussed in terms of the anatomical reorganization of the reproductive system and of the ventrolateral positioning of adult worker bee ovaries. (C) 2000 Wiley-Liss, Inc.
Keywords: Frieseomelitta varia; Lateral oviduct; Melipona quadrifasciata; Programmed cell death; Stingless bees; animal; apoptosis; bee; cytology; electron microscopy; growth, development and aging; larva; metamorphosis; oviduct; physiology; scanning electron microscopy; ultrastructure; Animals; Apoptosis; Bees; Larva; Metamorphosis, Biological; Microscopy, Electron; Microscopy, Electron, Scanning; Oviducts; Animalia; Apoidea; Frieseomelitta; Hexapoda